(untitled) (Modern education and development, 2025)
Virtualization technologies are now recognized as an essential component of modern information and communication systems. They enable the creation of multiple independent systems on a single hardware base and allow for their efficient and secure management. Virtualization not only simplifies IT infrastructure but also reduces costs and enhances system reliability. Additionally, it plays a crucial role in rapid recovery during emergencies, optimal resource utilization, and seamless integration with cloud environments. Emerging fields such as container technologies and edge computing are evolving based on virtualization. This article analyzes modern types of virtualization, their benefits, current challenges, and areas of practical application. Special attention is given to the role of virtualization in shaping the future of IT infrastructure.